Lifelong learning and the Roma minority in Central and Eastern Europe - Óhidy, Andrea; Forray, Katalin R. (Bingley, U.K. : Emerald Publishing Limited, 2019)
Access, attainment and success of Roma people in education are at a crisis point across Europe. Recent research has revealed that Roma people are the most underrepresented group in schools and other educational institutions. Policy makers across Central and Eastern Europe face the challenge of reversing the disadvantaged situation of the Roma minority. There is a whole host of policy strategies, measures and projects across Europe which offer similar solutions on national, regional and local levels. This book discusses the current educational climate and the impact of these policy measures for Roma people in eight Central and Eastern European countries: Bulgaria, Croatia, Czech Republic, Hungary, Moldova, Poland, Romania, and Slovakia. There is a severe lack of information about the Roma people in the public domain. This book seeks to raise awareness of this forgotten minority and evaluate the policies implemented to integrate the Roma people into the education system, using many different cultural perspectives written by experts across Central and Eastern Europe. This book will prove invaluable to those in the field of comparative education, educational leaders and practitioners in Central and Eastern Europe and beyond.
Introduction: lifelong learning and the Roma minority in Central and Eastern Europe / Katalin R. Forray and Andrea Óhidy -- Chapter 1. Bottom up, top down and human rights - Roma organizations, policy frameworks and European institutions / Natascha Hofmann -- Chapter 2. The Roma minority in the education system of Bulgaria / Milena Ivova Ilieva -- Chapter 3. The education situation of the Roma minority in Croatia / Goran Lapat and Renata Miljević-Riđički -- Chapter 4. Roma minority in the Czech Republic / Markéta Levínská, Dana Bitternová and David Doubek -- Chapter 5. Roma population in Hungary - focusing on educational opportunities / Julianna Boros and Eszter Gergy -- Chapter 6. Roma in the education system in the Republic of Moldova / Maria Diacon -- Chapter 7. The Roma community in Poland - the share of the population and its spatial distribution / Agnieszka Świętek and Wiktor Osuch -- Chapter 8. Lifelong learning for Roma in Romania / Aurora Adina Colomeischi -- Chapter 9. Education of the Roma minority in Slovakia / Rastislav Rosinský -- Conclusion: participation and success of Central and Eastern European Roma in education and lifelong learning: common challenge, similar solutions and hitherto unsatisfactory results / Andrea Óhidy.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Romanies -- Education -- Europe, Central; Romanies -- Education -- Europe, Eastern; Education, Adult & Continuing Education; Adult education, continuous learning